2012
DOI: 10.1038/mtna.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Specific Jak3 Downregulation in Lymphocytes Impairs γc Cytokine Signal Transduction and Alleviates Antigen-driven Inflammation In Vivo

Abstract: Jak3, one of the four members comprising the Jak family of cytosolic tyrosine kinases, has emerged as a promising target for nontoxic immunotherapies. Although a number of Jak inhibitors has already demonstrated efficacy, they suffer from secondary effects apparently associated to their pan-Jak activity. However, whether selective Jak3 inhibition would afford therapeutic efficacy remains unclear. To address this question we have investigated the immunosuppressive potential of selective Jak3 intervention in lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…plasmids and siRnAs. The sequences for siJAK3 were 5′-GGGUCCUUCACCAAGAUUU-3′ and 5′-CCAUGGUGCAGGAAUUUGU-3′ (Dharmacon Inc) 41 , and RNAiMAX (Invitrogen) was employed as the transfection reagent following the supplier's recommended protocol, where non-targeting siRNA (Dharmacon, D-001210-02-20) was the control. The MIG and the MIG-JAK3 (wild-type) plasmids were kindly provided by Dr. Kara Johnson at Oregon Health and Science University.…”
Section: Discussionmentioning
confidence: 99%
“…plasmids and siRnAs. The sequences for siJAK3 were 5′-GGGUCCUUCACCAAGAUUU-3′ and 5′-CCAUGGUGCAGGAAUUUGU-3′ (Dharmacon Inc) 41 , and RNAiMAX (Invitrogen) was employed as the transfection reagent following the supplier's recommended protocol, where non-targeting siRNA (Dharmacon, D-001210-02-20) was the control. The MIG and the MIG-JAK3 (wild-type) plasmids were kindly provided by Dr. Kara Johnson at Oregon Health and Science University.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a critical role for JAK1 was identified as STAT6 was activated by IL-4 or IL-13 through JAK1 in rat alveolar type II cells and airway epithelial cells were shown to require IL-4 signaling after allergen exposure (44, 45). Although a predominant role for JAK3 over JAK1 was suggested from siRNA knockdown experiments (46), intracellular enzymatic levels of JAK1 were shown to be higher than levels of JAK3 (47). This dissociation might reflect differences in individual JAK kinase binding capabilities to substrates or ligands versus enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, electroporation and nucleofection cause excessive cell death and may require preactivation of T cells and electrical apparatus [ 108 , 109 ]. Chemically modified synthetic siRNA with Acell agents can be transfected into primary T cells; however, they are needed to incubate with T cells for longer time and only a small portion of T cells are transfected [ 110 ]. The most disappointing defect of these methods is that it is difficult for them to be used in vivo .…”
Section: Targeting Th17 Cells By Cd4 Aptamer-ror γ mentioning
confidence: 99%